2021
DOI: 10.1186/s12864-021-07374-y
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the miRNA transcriptome of breast muscle from the embryonic to post-hatching periods in chickens

Abstract: Background miRNAs play critical roles in growth and development. Various studies of chicken muscle development have focused on identifying miRNAs that are important for embryo or adult muscle development. However, little is known about the role of miRNAs in the whole muscle development process from embryonic to post-hatching periods. Here, we present a comprehensive investigation of miRNA transcriptomes at 12-day embryo (E12), E17, and day 1 (D1), D14, D56 and D98 post-hatching stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Increasing evidence indicates that circRNAs can sequester relevant miRNAs through MREs to post-transcriptionally regulate gene expression. We identified 587 miRNAs in breast muscle at E12, E17, D1, D14, D56, and D98 in a previous study [ 28 ] (Table S 8 ). To investigate ceRNA regulation in muscle and identify muscle-related circRNAs, we identified putative miRNA-circRNA and miRNA-mRNA interactions using the 587 miRNAs and transcripts identified in profiles 3, 14, and 16.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that circRNAs can sequester relevant miRNAs through MREs to post-transcriptionally regulate gene expression. We identified 587 miRNAs in breast muscle at E12, E17, D1, D14, D56, and D98 in a previous study [ 28 ] (Table S 8 ). To investigate ceRNA regulation in muscle and identify muscle-related circRNAs, we identified putative miRNA-circRNA and miRNA-mRNA interactions using the 587 miRNAs and transcripts identified in profiles 3, 14, and 16.…”
Section: Resultsmentioning
confidence: 99%
“…The main mechanism of circRNA may be in acting as miRNA sponges to modulate post-transcriptional regulation [ 31 ]. Our previous studies have explored mRNA and miRNA expression at the same time points as the present research [ 11 , 28 ]. Therefore, we performed circRNA-miRNA-mRNA regulatory network construction using the circRNAs and mRNAs with the same expression pattern and the 587 miRNAs identified in the chicken muscle in our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Raw data were subjected to standardized analysis (Liu et al, 2021; Ma et al, 2018). Adapter dimers, low‐quality reads, junk reads, common RNA families (mRNA, rRNA, tRNA, snRNA, and snoRNA), and repeats were removed by using the ACGT101‐miR program (LC Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…MiRNAs play important role in the regulation of cellular signal networks in both normal and diseased conditions. In eukaryotes, 2/3 of the coding genes are regulated by miRNAs [11], which participate in the regulation of many physiological processes [12], such as development, cell division, proliferation, and metabolism, and play an essential role in the in ammatory response [13], immune-related pathway [14], tumorigenesis [15] and so on. A growing number of studies have shown that host miRNAs modulate target gene expression at the post-transcriptional level by inhibiting translation and promoting degradation of target genes, and play an important role in against parasite infection [16,17].…”
Section: Introductionmentioning
confidence: 99%